Hágsater, E., M. Á. Soto Arenas, G. A. Salazar Chávez, R. Jiménez Machorro, M. A. López Rosas y R. L. Dressler. 2005. Las orquídeas de México. Instituto Chinoín México, D.F. 304 pp - González Tamayo, Roberto (Instituto de Ecología, A.C., 2022)
Reseña de libro.